Predicting Neoplastic Progression in Barrett's Esophagus - Wang, Jean S. (2010)
Patients with Barrett's esophagus have a significantly increased risk of esophageal adenocarcinoma, 40-125 times higher than the general population. Since only a small fraction of Barrett's esophagus patients will actually progress to esophageal adenocarcinoma, there is a need to develop markers that may accurately predict which patients with Barrett's esophagus are likely to have aggressive disease and progress to cancer versus patients who will remain histologically stable and have a benign course. This would allow for better risk stratification of patients with Barrett's esophagus in order to target aggressive surveillance and intervention towards only those patients at highest risk for neoplastic progression. Predictive biomarkers may thus have significant clinical utility in the management of Barrett's esophagus patients. The detection of dysplasia in esophageal biopsies is currently the only standard method used in clinical practice as a marker for increased risk of cancer. However, dysplasia has not been a accurate or reliable marker for predicting malignant progression and suffers from poor interobserver agreement among pathologists and sampling error. A multitude of potential biomarkers have been studied over the years. It is likely that the best model for predicting progression to esophageal adenocarcinoma in Barrett's esophagus patients will ultimately involve a combination of biomarkers, dysplasia grade and other pathological characteristics, as well as clinical and demographic attributes. In this review, we will discuss the most promising biomarkers that have been studied thus far.